2012
DOI: 10.1111/j.1364-3703.2012.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

The conserved oligomeric Golgi complex is involved in penetration resistance of barley to the barley powdery mildew fungus

Abstract: Membrane trafficking is vital to plant development and adaptation to the environment. It is suggested that post-Golgi vesicles and multivesicular bodies are essential for plant defence against directly penetrating fungal parasites at the cell wall. However, the actual plant proteins involved in membrane transport for defence are largely unidentified. We applied a candidate gene approach and single cell transient-induced gene silencing for the identification of membrane trafficking proteins of barley involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 64 publications
4
65
0
1
Order By: Relevance
“…Moreover, several SNPs were repeatedly found to be significantly associated with chemical features of these three metabolites (Figure 6a). SNP loci with multiple significant associations (labeled yellow; Figure 6) within this associated group were as follows: B506_11, B1401_69 (aligned to gene encoding for oligomeric Golgi complex; Ostertag, Stammler, Douchkov, Eichmann, & Hückelhoven, 2013), B447_54, B977_86, B982_75 (aligned to gene encoding for lectin‐domain receptor kinase; Singh & Zimmerli, 2013), B536_31, B1327_41, and B440_76 (aligned to gene encoding for a protein sensitive to rhizotoxicity; Sawaki et al., 2009; Fan, Lou, Yang, & Zheng, 2016). Several of these SNPs (B1401, B982_75, B440_76, B1401_69, B447_54, and B977_86) also showed evidence of being under selection in Pais et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several SNPs were repeatedly found to be significantly associated with chemical features of these three metabolites (Figure 6a). SNP loci with multiple significant associations (labeled yellow; Figure 6) within this associated group were as follows: B506_11, B1401_69 (aligned to gene encoding for oligomeric Golgi complex; Ostertag, Stammler, Douchkov, Eichmann, & Hückelhoven, 2013), B447_54, B977_86, B982_75 (aligned to gene encoding for lectin‐domain receptor kinase; Singh & Zimmerli, 2013), B536_31, B1327_41, and B440_76 (aligned to gene encoding for a protein sensitive to rhizotoxicity; Sawaki et al., 2009; Fan, Lou, Yang, & Zheng, 2016). Several of these SNPs (B1401, B982_75, B440_76, B1401_69, B447_54, and B977_86) also showed evidence of being under selection in Pais et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these candidate SNPs occurred on loci with predicted functions related to disease resistance. Some SNP loci such as B1401 may encode for proteins (i.e., an oligomeric Golgi complex) that facilitate glycosylation to inhibit disease (Ostertag et al., 2013). Other loci such as F ST outlier B982 (Pais et al., 2016) are predicted to encode for signaling receptors like lectin‐domain receptor kinases, which have been previously implicated in plant immunity responses among other signaling processes (Singh & Zimmerli, 2013), and recent functional experimentation on resistance genes encoding for such receptors in Solanaceous plants has provided evidence for resistance against Phytophthora disease (Wang, Weide, Govers, & Bouwmeester, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This way, AtEXO70H4 was shown to be indispensable for correct trichome cell wall thickening and callose deposition (Kulich et al, 2015). The results of gene-silencing experiments suggest that the EXO70F-like subunits are essential in resistance to fungal penetration in barley (Hordeum vulgare; Ostertag et al, 2013). To our knowledge, no study simultaneously showing the localization of more EXO70 isoforms in a single cell has been published so far.…”
mentioning
confidence: 87%
“…hordei fungus. 18 A recent study by Kulich and colleagues showed that Exo70B1 could contribute to autophagy. 19 Plants displaying extended cell death lesions also hyper-accumulated SA.…”
Section: Introductionmentioning
confidence: 98%